2011
DOI: 10.1007/s00380-011-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cardio-ankle vascular index (CAVI) and coronary artery calcification (CAC) in patients with type 2 diabetes mellitus

Abstract: Early detection of atherosclerosis is important for patients with type 2 diabetes mellitus because cardiovascular disease (CVD) is a main cause of death in these people. In this study, we investigated the relationship between an arterial stiffness parameter called cardio-ankle vascular index (CAVI) and coronary artery calcification (CAC). We performed a cross-sectional study in 371 type 2 diabetic patients with clinical suspicion of coronary heart disease (CHD). We evaluated the relationships between CAVI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
(24 reference statements)
1
25
0
7
Order By: Relevance
“…The study result suggested that coronary artery calcification was an independent predictor of mortality in diabetes independent of diabetes duration and control and conventional cardiovascular risk factors. In another cross-sectional study with 371 patients with type 2 diabetes, CAVI was also correlated with age and log (CACS 1) 29) but not fasting plasma glucose and hemoglobin A1c. Our findings were consistent with these studies.…”
Section: Cardio-ankle Vascular Indexmentioning
confidence: 88%
See 2 more Smart Citations
“…The study result suggested that coronary artery calcification was an independent predictor of mortality in diabetes independent of diabetes duration and control and conventional cardiovascular risk factors. In another cross-sectional study with 371 patients with type 2 diabetes, CAVI was also correlated with age and log (CACS 1) 29) but not fasting plasma glucose and hemoglobin A1c. Our findings were consistent with these studies.…”
Section: Cardio-ankle Vascular Indexmentioning
confidence: 88%
“…CAVI is easy to measure, unaffected by blood pressure, and superior in reproducibility compared with pulse wave velocity. Several reports have shown that CAVI is associated with atherosclerotic disease 23,[25][26][27][28] , which is also considered to be a useful method to detect coronary artery calcification 29) . CAVI may be more cost effective compared with CAC score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Действительно, при изучении СЛСИ у больных ИБС достаточно убедительно показана его связь с рас-пространенностью коронарного атеросклероза [3,10,11]. Так, у больных сахарным диабетом 2-го типа СЛСИ позитивно коррелировал с кальциевым индек-сом коронарных артерий, определяемым при мульти-спиральной компьютерной томографии (r=0,303, p<0,0001) [10].…”
Section: Discussionunclassified
“…Так, у больных сахарным диабетом 2-го типа СЛСИ позитивно коррелировал с кальциевым индек-сом коронарных артерий, определяемым при мульти-спиральной компьютерной томографии (r=0,303, p<0,0001) [10]. Также есть свидетельства о наличии связи между СЛСИ и распространенностью [11] и выраженностью коронарного атеросклероза [6,9,12,13].…”
Section: Discussionunclassified